Rejections of Knowledge Economy and/or New Economy - Gürdal, Oya (Information World, 2004)
The techno-economic transformation currently experienced has led to definea well-known value on the level of today’s comprehension as a new fact, of which we were aware of its potential, believed in its necessity, yet due to our insufficient comprehension could not so far utilise it extensively. Knowledge and/or information, in addition to their contributions to technology output have profoundly changed both the processes of our daily lives and those in business world. Actually, what makes economy knowledge-based depends on how we comprehend knowledge and/or information. In this study, the issue of knowledge and/or information economy is taken under consideration with special emphasis upon its rejections. In this realm techno-economic transformation, anticipations concerning dimensions of transformation, the evaluation of all related challenges and opportunities of the knowledge economy were discussed. Knowledge economy is a product of transformation. Therefore, the opportunities and challenges embedded in choices should be defined rationally. The study also calls for intellectual effort on deciding upon choices for knowledge-based economy goals in real life.
Keywords: Knowledge economy; Knowledge management; Information management